Application of Robots to Improve Social and Communication Skills among Autistic Children - Ismail, M.Z.; Azaman, N. I. L.; Khalid, N.K (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Autism Spectrum Disorder (ASD) typically appears during the first three years of life. It exhibits certain characteristics such as impairment in social interaction and communication skill. This paper analyzed the use of robots in augmenting social and communication skills among ASD children. The features and characteristics of seven widely used robots and their impacts were included. There are variety of robots worldwide being used as therapy assistants in ASD therapy with multiple functions and appearances. Thus, future study can focus on how to combine the features and advantages of each robot to create more efficient robots in helping children with ASD.